79 Long-term outcomes of supraventricular tachycardia ablation in congenital heart disease: single centre uk experience. (5th June 2017) - Sawhney, Vinit; McLellan, Alex; Perera, Dhanuka; Izquierdo, Dionisio; Babra, Deshveer; Schilling, Richard; Lambiase, Pier; Lowe, Martin; Ezzat, Vivienne
Abstract : Introduction: Catheter ablation for supraventricular tachycardia (SVT) in patients with congenital heart disease (CHD) is an important therapeutic option, which is safe and effective. Ablation outcomes vary significantly with increasing complexity of cases and data is limited. We reviewed the safety and long-term efficacy of SVT ablation in CHD patients and examined the differences in outcomes of simple and complex cases in a leading UK centre. We also examined the predictors of arrhythmia recurrence post ablation. Methods and Results: Consecutive patients undergoing SVT ablation from 2007–2015 from an independent prospective CHD registry were included. SVTs included AFl (typical/incisional/atypical), AVNRT and AVRT. Medical records were reviewed and patients were contacted for follow-up. 131 ablation procedures in 110 patients were included. Patients were divided into three groups based on complexity of cases. Group A (Simple CHD) – ASD/VSD/Valve disease, Group B (CHD of moderate complexity) – Fallots/Ebstein/Other and Group C (CHD of great complexity) – Fontan/Mustard/Total Cavopulmonary Connexion. Manual mapping and ablation was carried out in all cases using 3D electroanatomic mapping systems. The mean age of the cohort was 42 years and 52% of the patients were men. 41% of cases were in Group C. Nearly half the procedures were carried out under general anaesthetic (49%) with mean procedure and fluoroscopy times of 4 and 1 hours respectively. Acute ablation success was 95%, with failure to terminate arrhythmia in three, unsuccessful transbaffle puncture in one and post-procedure complications in three patients (retroperitoneal haematoma, tamponade, CHB). Over a mean follow-up of 2 years, 78% patients remained arrhythmia free. The mean arrhythmia recurrence time was 14 months. Two deaths were noted. Arrhythmia-free survival between the groups was not statistically significant (A, B, C; 76.5, 76.6, 72.2%; p 0.9, 0.6, 0.6). There was a trend towards longer procedure times with increasing case complexity however this did not reach significance. Presence of AF (entire cohort) and LA diameter (Group C) correlated with arrhythmia recurrence (p=0.06, 0.05). Conclusion: SVT ablation in context of CHD is safe and effective irrespective of the complexity of underlying anomaly. However, late recurrence is not uncommon. Presence of AF and atrial size is likely to predict outcome. There is scope to improve long-term single procedure efficacy (especially in complex cases) by using new technologies.